Kopie van exemplaar bij Dir.Gen. van de Arbeid, Den Haag. Kistjesstoffeerderij, leeftijd 13-15 jaar, gemiddeld weekloon f6,50-8,-
Kopie van exemplaar bij Dir.Gen. van de Arbeid, Den Haag. Kistjesstoffeerderij, leeftijd 13-15 jaar, gemiddeld weekloon f6,50-8,-.